1996
DOI: 10.1042/cs0900235
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Sinus Arrhythmia and Central Respiratory Drive in Humans

Abstract: 1. The influence of central inspiratory drive on heart rate variability was investigated in young human subjects using power spectral analysis of R-R intervals. 2. The area of the high-frequency component occurring at the respiratory frequency (0.2-0.25 Hz) in the power spectral density curves was used as an index of respiratory sinus arrhythmia. 3. Central inspiratory drive was increased by breathing a CO2-enriched (5%) gas mixture and this condition was compared with a similar degree of ventilation produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…During atrial pacing, it appears that respiratory-related oscillations in HR can contribute to respiratory oscillations in blood pressure (2,28). Furthermore, there is evidence that respiratory centers within the central nervous system can directly influence HR independently of changes in blood pressure (1). However, in the present study, we found that the changes in HR due to either vagal or sympathetic activity slightly reduced the gain of the transfer function between PRBS stimulus and arterial pressure but not the general shape of the profile.…”
Section: Identification Of Model Under Open-loop Conditionsmentioning
confidence: 99%
“…During atrial pacing, it appears that respiratory-related oscillations in HR can contribute to respiratory oscillations in blood pressure (2,28). Furthermore, there is evidence that respiratory centers within the central nervous system can directly influence HR independently of changes in blood pressure (1). However, in the present study, we found that the changes in HR due to either vagal or sympathetic activity slightly reduced the gain of the transfer function between PRBS stimulus and arterial pressure but not the general shape of the profile.…”
Section: Identification Of Model Under Open-loop Conditionsmentioning
confidence: 99%
“…Although the LF and HF components evaluate the influences of the autonomic system on the sinus node, their specificity as autonomic markers is incomplete because HRV also depends on other factors. Furthermore, the LF component is also influenced by the parasympathetic system (20,21). However, the passive postural change used in this study allows a better evaluation of sympathetic influence on HRV (9).…”
mentioning
confidence: 99%
“…The characteristic CO 2 dependency of whatever causes the central respiratory rhythm (2,12,24,30) uniquely distinguishes it from other oscillators that may also exist in the central nervous system (CNS) (24) that may also oscillate at "respiratory frequencies" (without causing the central respiratory rhythm) and that influence autonomic activity during breath holding. We therefore tested whether any of the frequency components of sinus arrhythmia were reduced by a prior reduction in PCO 2 at the start of breath holding and were stimulated by the linear rise in PCO 2 throughout breath holding with preoxygenation (34).…”
mentioning
confidence: 99%